Entre instrumentos musicales, ritos y muerte en Garza, Nicoya, Guanacaste (G-752 Rj) - Guerrero Miranda, Juan Vicente (2012)
This article makes reference to the archaeological data obtained in the Rempujo Site, in the Peninsula of Nicoya, Costa Rica. This work has allowed to relevant information about funerary patterns, types of burials, and the association of a series of pre-Hispanic artefacts, linked to diverse activities that people carried out circa 2000 years ago. From the recovered artifacts, musical instruments (ocarinas, whistles), jade pendants, war and ceremonial maces and axes stand out, broading our knowledge of the mortuary features and materials found in the regional context.